2020
DOI: 10.2147/cmar.s251820
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA SLC25A21-AS1 Promotes Multidrug Resistance in Nasopharyngeal Carcinoma by Regulating miR-324-3p/IL-6 Axis</p>

Abstract: Background: Nasopharyngeal carcinoma (NPC), one of the most common types of head and neck tumor, occurred in the epithelial lining of the nasopharynx and is mainly prevalent in Southeast Asia and Southern China. However, the molecular mechanisms of NPC multidrug resistance still remained largely unclear. Methods: The qRT-PCR assay was performed to examine SLC25A21-AS1, miR-324-3p and IL-6 expression in NPC tissues and cell. The CCK8 assay and colony formation assay were used to detect cell growth. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…In addition, a previous study showed that SLC25A21‐AS1 is associated with multidrug resistance 27 . The present study demonstrated that the rate of cisplatin‐induced apoptosis was significantly increased in SLC25A21‐AS1 ‐knockdown cells and decreased in SLC25A21‐AS1‐overexpressing cells (Figure 8F).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, a previous study showed that SLC25A21‐AS1 is associated with multidrug resistance 27 . The present study demonstrated that the rate of cisplatin‐induced apoptosis was significantly increased in SLC25A21‐AS1 ‐knockdown cells and decreased in SLC25A21‐AS1‐overexpressing cells (Figure 8F).…”
Section: Resultssupporting
confidence: 74%
“…67,68 A previous study indicated that SLC25A21-AS1 is associated with multidrug resistance. 27 The present study demonstrated that SLC25A21-AS1 overexpression conferred resistance to cisplatin-induced apoptosis, whereas SLC25A21-AS1 knockdown enhanced chemosensitivity. Currently, antisense oligonucleotides, RNA interference (RNAi) technology, small molecule inhibitors, and CRISPR/Cas9 are therapeutic strategies targeting lncRNAs.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, these findings are of great significance to explore the pathogenesis and treatment of CML. Some literatures have shown that ceRNA network participates in the occurrence of MDR in cancers, including nasopharyngeal carcinoma (Wang et al, 2020) and AML (Yu et al, 2020). However, except for one paper (Zhang et al, 2019), there is no other report on ceRNA regulatory network and its role in MDR-CML.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high expression of SLC25A21-AS1 could target miR-324-3p and thus mediate IL-6, resulting in enhanced proliferation and multidrug resistance in NPC cells. 101 It has been reported that lnc C00346 targets miR-342-5p and reduces the sensitivity of nasopharyngeal carcinoma cells to cisplatin. 102 In addition, a variety of lncRNAs may be involved in the regulation of chemotherapy sensitivity in nasopharyngeal carcinoma ( Table 2 ).…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%
“… 105 In addition, lnc SLC25A21-AS1 regulates IL-6 by targeting miR-324-3p, making nasopharyngeal carcinoma resistant to multiple chemotherapeutic agents. 101 Li et al revealed that lnc DLEU1 inhibits miR-381-3p, resulting in increased expression of BIRC6 and increased resistance of nasopharyngeal carcinoma to the chemotherapeutic agent cisplatin. 95 Lin et al demonstrated that silencing lncRNA HOXA11-AS can inhibit the c-Met/AKT/mTOR pathway by specifically upregulating miR-454-3p, thus promoting cell apoptosis and enhancing the sensitivity of cisplatin-resistant NPC cells to cisplatin.…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%